Fifty Years of Operating Systems. - Denning, Peter J. (Communications of the ACM, 2016)
The author reflects on the evolution of operating systems. Topics covered include a brief history of operating systems, the four stages of an operating system and highlights of various research made on operating systems. He discusses the eight principles which serve as the foundation for the generation of operating systems, wherein the principles include interactive computing, interrupt systems and modular programming.